Writing dissertation and grant proposals epidemiology, preventive medicine and biostatistics [electronic resource] - Chasan-Taber, Lisa (CRC Press/Taylor and Francis, 2014)
Competition for research funds in epidemiology, preventative medicine, and biostatistics has never been more intense and, at the same time, the grant application and review process at such agencies as the National Institutes of Health (NIH) is undergoing significant transformation. Writing Dissertation and Grant Proposals: Epidemiology, Preventive Medicine and Biostatistics targets effective grant proposal writing in this highly competitive and evolving environment. Covering all aspects of the proposal writing process, the text:Provides summary checklists and step-by-s.